Altitudinal distribution of subaerial species of Mesotaenium microalga (Zygnematophyceae, Streptophyta) from the Southern Tropical Andes of Peru - Montoya T., Haydee; Museo de Historia Natural. Departamento de Simbiosis Vegetal. Facultad de C. Biológicas UNMSM; Facultad de Ciencias Biológicas. Universidad Ricardo Palma (2023)
The Tropical Peruvian Andes host  a great ecosystem diversity such as the montane cloud forest at the southern east slopes. The subaerial moist habitats  along the Alccamayo creek  belong to Aguas Calientes,  Cusco . They were evaluated  in  winter (august 2017) between 2184  and 3000 m of elevation with the  mean temperature between 16 and 18°C. In the southern  highland Andean, the  cryosphere of  the  Allincapac glaciers, Carabaya  Cordillera, Puno,  was evaluated  in summer season (february 2018) between 4500 and 4700 m elevation. The thermogradients were between 0 and 10°C and pH between 6.0 and 6.5. Collections of subaerophytic assemblages with litophilic, and  chasmolithic microalgae and cyanobacterial  were carried out  by scraped the biofilms or crusts from the cliffs of  calcareous  rock  surfaces  or ice layers. Highland colonization (Allincapac  glacier) by the  cryophilic  streptophyte  Mesotaenium  berggrenii morphospecies  showed  its adaptation to freeze and desiccation conditions as well as deglaciation and hydrated periods. At tropical lowland elevation gradient the Andean mesophilic species   M. macrococcum, and M. chlamydosporum were recognized by its morphotypes (colonial, unicells) as well  as  survival strategies and propagation (complex extracellular polymers, chromatic adaptation).  M. berggrenii, M. macrococcum, and M. chlamydosporum are new record species for the Peruvian microalgae flora.